The sociology of gender : an introduction to theory and research - Wharton, Amy S. (Wiley-Blackwell, 2012)
"Featuring extensive revisions and updates, the new Second Edition of The Sociology of Gender presents an introductory overview of gender theory and research, and continues to offer a unique and compelling approach to one of the most important topics in the field of sociology. Drawing from recent and ongoing research in the field, gender scholar Amy Wharton develops and expands upon theoretical approaches to gender from her acclaimed first edition. These approaches emphasize how gender can be viewed through different "lenses," and how each one generates a particular way of thinking about gender and its role in social life. Wharton shows how individualist approaches view gender as part of the person; interactional approaches focus on the ways that gender emerges through social interaction; and institutional views emphasize how gender is built into organizations, social structures, and institutional arrangements. The book deftly summarizes and examines these three frameworks to facilitate an understanding of gender's contested meanings and vast areas of research. Also addressed is the importance of analyzing gender in relation to other kinds of distinctions, such as those based on race, social class, or sexual orientation. The newest research findings by key scholars are also discussed, and excerpts from contemporary scholarship and public debate allow for comparative analysis of different areas of study. The Sociology of Gender: An Introduction to Theory and Research, Second Edition, offers the most up-to-date and accessible overview of this prominent subfield of sociological enquiry available today"